An Asset Administration Shell Method for Data Exchange Between Manufacturing Software Applications - Xun Ye; Mengmeng Yu; Won Seok Song; Seung Ho Hong (IEEE Access, 2021)
The multifaceted industrial application of cyber-physical systems (CPSs) has increased, enabling tight interactions between physical and computational elements. Industry 4.0 aims to promote industrial application of CPSs. The asset administration shell (AAS) represents the practical embodiment of the CPS, and can be obtained by integrating information and communication technologies. Most prior studies concentrated on AASs for hardware assets in the manufacturing domain; they seldom considered AASs for software applications. To fill this gap, we present a method for implementing AASs for software, i.e., a manufacturing execution system (MES) combined with an enterprise resource planning (ERP) system. This method allows runtime data exchange between an MES and ERP; this is better than the conventional file-based method. Finally, a data exchange case (a manufacturing order) is presented to validate our AAS method.